Monetary and macroprudential policies - Paolo Angelini; Stefano Neri; Fabio Panetta (European Central Bank (ECB), 2012)
We use a dynamic general equilibrium model featuring a banking sector to assess the interaction between macroprudential policy and monetary policy. We find that in “normal” times (when the economic cycle is driven by supply shocks) macroprudential policy generates only modest benefits for macroeconomic stability over a “monetary-policy-only” world. And lack of cooperation between the macroprudential authority and the central bank may even result in conflicting policies, hence suboptimal results. The benefits of introducing macroprudential policy tend to be sizeable when financial shocks, which affect the supply of loans, are important drivers of economic dynamics. In these cases a cooperative central bank will “lend a hand” to the macroprudential authority, working for broader objectives than just price stability in order to improve overall economic stability. From a welfare perspective, the results do not yield a uniform ranking of the regimes and, at the same time, highlight important redistributive effects of both supply and financial shocks.
Keywords: E44; E58; E61; 330; capital requirements; Macroprudential policy; monetary policy